Electronic Seminar - Geidarov, P.Sh. (Science and Innovation, 2024)
The structure of electronic scientific seminar, which provides high-quality and unbiased evaluation of research papers, including thesis research, has been described. Conditions for the implementation of electronic scientific seminar have been considered.